Effect of Mobilization with Movement and Kinesio Taping on Knee Function and Pain in Gonarthrosis - Tomas Pažemeckas; Giedrė Jurgelaitienė; Laura Janaušonienė (Lithuanian Sports University, 2022)
Background.  Gonarthrosis is one of the most common diseases of the musculoskeletal system. As the disease progresses, the patient's social and physical activities change. Reliable and effective therapies that slow the progression of gonarthrosis have not yet been found. There is a lack of evidence that a short course of physiotherapy and exercise-based treatment is effective or of how mobilization with movement and kinesio taping affects knee function and pain. We believe that in patients with knee gonarthrosis, the positive effects of physiotherapy combined with mobilization with movement and kinesio taping on knee functions and pain will be better than in those subjects who received only traditional physiotherapy. Aim. To determine the effect of mobilization with movement and kinesio taping on knee function parameters and pain in gonarthrosis. Methods. The study included 22 people diagnosed with gonarthrosis. For the experimental group (n=11), physiotherapy exercise, mobilization with movement and kinesiotape were applied, whereas the control group (n=11) used only physiotherapy exercise procedures. Subjects were evaluated for pain intensity, active knee range of motion, dynamic knee joint stability and evaluation of thigh muscle strength. Results. In the experimental group, there was a significant decrease in pain after 7 days and a significant difference with control group. Significant knee flexion results were recorded in the experimental group and significant knee extension results were recorded in the control group. In the experimental group, the dynamic knee joint stabilization significantly increased after 14 days. The strength of the thigh muscles was significantly increased in the experimental group after 14 days. Conclusion. The effect of mobilization with movement and kinesio taping of knee function, dynamic stability pain improving functional performance of dynamic stability was more significant than an exercise program lasting two weeks in subjects with knee gonarthrosis. Keywords: gonarthrosis, mobilization with movement, kinesio taping.